IMPLEMENTASI PELAYANAN AIR MINUM DI PERUSAHAAN DAERAH AIR MINUM TIRTA KHATULISTIWA - Supartagus E.21109058 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study were 1) the quality of water flowing to the customer is still not entirely good or contained residues (waste) water treatment flow to customers, 2) during the dry season, water services are often substandard, so that customers receive water service of PDAM Tirta Equator .. The results showed that (1) water services by the Regional Water Company (PDAM) Tirta Equatorial Pontianak still felt less than optimal, (2) the availability of water does not last all year, because it depends on the supply of the season, (3) the quality of treated water , residue processing, raw material availability and utilization of services less Informatics going well. Fenomayan addressing any author gives fekomendasi that communication can take place in both directions, the PDAM Tirta Equatorial Pontianak should improve the transmission of each policy, the potential use of the media (internet) and carried out in a programmed, in addition should also take advantage of PDAM Tirta Equatorial cheap communication media such as internet to deliver the policy.Keywords: Implementation, Services, Drinking Water